If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = 2x + -3 Reorder the terms: 7 + -3x = -3 + 2x Solving 7 + -3x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + -3x + -2x = -3 + 2x + -2x Combine like terms: -3x + -2x = -5x 7 + -5x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + -5x = -3 + 0 7 + -5x = -3 Add '-7' to each side of the equation. 7 + -7 + -5x = -3 + -7 Combine like terms: 7 + -7 = 0 0 + -5x = -3 + -7 -5x = -3 + -7 Combine like terms: -3 + -7 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| [y-3][y+2]=0 | | x^2+9=16 | | p^2=81 | | 6=14-2y | | 500=23x | | .83x+.5=.25(x-4) | | x+(-23)=-90 | | Y-4=-2(x+7) | | 8x-10=11+11x | | x+21=3x+5 | | 2k^2+3k-9=0 | | 25=3s-4(20-s) | | 4x+11=-2x-7 | | ab^9= | | -2x=-116 | | 6r^2+11r+3=0 | | -12t+6+7t=8t-3 | | 3x-6-2x+1=-12 | | 12a^2+11a-5=0 | | 5x-2x=27 | | 8x+5=9x-12 | | -2=-4(-7+1)+5(8+2y) | | 5-5(a+2)=7+a | | 6z^2+19z+10=0 | | x/(-2)=-61 | | (4x+1)(3x-2)=0 | | 3s-2=5s-6 | | -3r-13r=2 | | 5v^2+15v-50=0 | | 80-x=91 | | 16n+8=49n+67 | | x/(-4)=-34 |